2016
DOI: 10.1177/0898010116652974
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Relationship Between Nurses’ Views on Spirituality and Spiritual Care and Their Level of Burnout

Abstract: Nurses' burnout levels increased with the increase in their spirituality and spiritual care mean scores. This situation can be associated with the fact that providing spiritual care increases nurses' workload. Therefore, similar studies are recommended to be conducted with wider groups of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…The majority of studies that found a significant association between gender and burnout reported that female gender was a significant predictor of increased risk for burnout [38, 48, 52, 81, 89, 103, 105, 117, 125, 163, 165, 168, 173]. .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies that found a significant association between gender and burnout reported that female gender was a significant predictor of increased risk for burnout [38, 48, 52, 81, 89, 103, 105, 117, 125, 163, 165, 168, 173]. .…”
Section: Resultsmentioning
confidence: 99%
“…In various studies, nurses considered themselves incompetent in providing spiritual care owing to grim working conditions, 8 inadequate information provided during their education and inability to find free time for getting trained on the subject. Similarly, Herlianita et al 9 reported that nurses' specialty, education level, clinical seniority, spiritual training background, and experience in providing spiritual care had an impact on their Spirituality and Spiritual Care Rating Scale (SSCRS) scores.…”
Section: Introductionmentioning
confidence: 99%
“…6 The positive attitudes of nurses, such as having a sense of compassion towards patients, showing sufficient patience to listen to the patients, and taking enough time to fulfill their caregiver role increase the effectiveness of the treatment process. 7 In various studies, nurses considered themselves incompetent in providing spiritual care owing to grim working conditions, 8 inadequate information provided during their education and inability to find free time for getting trained on the subject. Similarly, Herlianita et al 9 reported that nurses' specialty, education level, clinical seniority, spiritual training background, and experience in providing spiritual care had an impact on their Spirituality and Spiritual Care Rating Scale (SSCRS) scores.…”
Section: Introductionmentioning
confidence: 99%
“…A espiritualidade é um fenômeno humano universal, mas o nível de consciência acerca desta sofre variação, de maneira que algumas pessoas expressam-na de forma mais perceptível que outras (4) . Porém, como já mencionado, existe uma linha tênue entre a percepção clara do que é religiosidade e do que é espiritualidade.…”
Section: Discussionunclassified
“…Em relação ao cuidado, a enfermagem é uma profissão que pressupõe grande proximidade entre as pessoas e esse contato requer do profissional capacidade e sensibilidade para lidar com todas as dimensões humanas, tais como biológica, mental, emocional e espiritual. Assim, frente a influência que a dimensão espiritual exerce sobre a vida das pessoas, torna-se de suma importância que haja conhecimento por parte da equipe de enfermagem sobre questões relacionadas à espiritualidade e à religiosidade para a oferta de um cuidado eficaz (4) .…”
Section: Introductionunclassified